Neutrophil-to-lymphocyte ratio as a predictor of low cardiac output syndrome after open heart surgery in children with congenital heart disease - Laila, Dewi S.; Perdana, Andri; Permatasari, Ruth K.; Kadim, Muzal; Advani, Najib; Supriyatno, Bambang; Chozie, Novie A.; Djer, Mulyadi M. (Narra Sains Indonesia, 2024)
Neutrophil-to-lymphocyte ratio (NLR) as a predictor in determining low cardiac output syndrome (LCOS) has not been widely reported. The aim of this study was to explore the role of pre-surgery, 0-, 4-, and 8-hour post-surgery NLR as predictors of LCOS incidence after open heart surgery in children with congenital heart disease (CHD). This study used a prognostic test with a prospective cohort design and was conducted from December 2020 until June 2021 at the cardiac intensive care unit (CICU) of Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. The subject consisted of children aged one month to 18 years who underwent open heart surgery using a cardiopulmonary bypass (CPB) machine. A receiver operating characteristic curve was applied to identify the predictive performance of NLR for poor outcomes (LCOS incidence). Out of 90 patients included in the study, 25 (27.8%) of them developed LCOS between 3 to 53 hours post-surgery. All NLR values (pre-surgery and 0-, 4-, and 8-hours post-surgery) were associated with the incidence of LCOS. Pre-surgery NLR (cut-off value ≥0.88) had a fair predictive value (area under curve (AUC) 70; 95%CI: 57–83) for predicting LCOS incidence with sensitivity and specificity of 64% and 64.62%, respectively. NLR 0-hour post-surgery (cut-off value ≥4.73) had a good predictive value (AUC 81; 95%CI: 69–94) for predicting LCOS incidence, with 80% sensitivity and 80% specificity. NLR 4- and 8-hours post-surgery had very good predictive values (AUC 97%; 95%CI: 92–100 and 98; 95%CI: 94–100, respectively), with cut-off values ≥6.19 and ≥6.78, had the same 92% sensitivity and the same 96% sensitivity. The presence of LCOS was associated with mortality (odds ratio of 5.11 with 95%CI: 3.09–8.46). This study highlights that pre-surgery, 0-, 4-, and 8-hours post-surgery NLR can be predictors of LCOS after open heart surgery in children with CHD.